Development of an Ethnoscience-Based Interactive Educaplay Game to Improve Students’ Problem-Solving Skills - Juwitaningrum, Juwitaningrum; Buchori, Achmad; Sumarno, Sumarno (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2025)
This study aims to develop an Ethnoscience-integrated Educaplay interactive learning game that is valid, practical, and effective in enhancing elementary students’ problem-solving abilities (PSA). This study adopted the Research and Development (R&D) method using the Dick and Carey development model, comprising nine systematic stages. The research subjects were fourth-grade students at SD Negeri Pranti (as the experimental class) and SD Negeri Pragu (as the control class) in Sulang District, Rembang Regency. Product validation was conducted by two experts (media and material experts), while practicality testing was measured through teacher and student response questionnaires. Effectiveness testing was measured using a Pretest Posttest Control Group Design and analyzed via the N-Gain Score. The results showed that the developed product is highly feasible and valid for use, with an average media expert validity reaching 98.96% and material expert validity 99.48%, both falling into the Very Valid category. Practicality testing also yielded high responses from students (92%) and teachers (91%), confirming the product is Very Practical. The key finding is the effectiveness test result, where the average N-Gain score in the experimental class reached 77.74 (or 0.7774), which is classified in the high category. This significant increase indicates that the Ethnoscience-based Educaplay Interactive Game effectively boosts students' problem-solving ability through a relevant and interactive learning context.